Civil Challenges to the Use of Low-Bid Contracts for Indigent Defense - Lemos, Margaret H. (2000)
In recent years, increasing attention has been directed to the problem of adequate representation for indigent criminal defendants. While overwhelming caseloads and inadequate funding plague indigent defense systems of all types, there is a growing consensus in the legal community that low-bid contract systems-under which the state or locality's indigent defense work is assigned to the attorney willing to accept the lowest fee-pose particularly serious obstacles to effective representation. In this Note, Margaret Lemos argues that the problems typical of indigent defense programs in general-and low-bid contract systems in particular-can and should be addressed through § 1983 civil actions alleging that systemic defects in the state or locality's chosen method for providing indigent defense services constitute a violation of indigent defendants' constitutional right to effective assistance of counsel Lemos concludes that, by addressing the causes of ineffective assistance, such an approach can achieve positive change in a way that case-by-case adjudication of postconviction claims of ineffective assistance cannot